Peran Mediasi Emotional Exhaustion pada Pengaruh Work Life Balance terhadap Kepuasan Kerja Karyawan Wanita di Universitas Negeri Surabaya - Sihaloho, Cici Novita; Indawati, Nurul (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
The factors that influence employee job satisfaction are work-life balance and emotional exhaustion.Â Factors that can affect job satisfaction will affectÂ employee job satisfaction.Â This study aimed to determine the influence of work-life balance on job satisfaction through emotional exhaustion. This research was conducted at Surabaya State University, with a total sample of 60 employees and used convenience sample techniques. Data collection uses surveys, interviews, and questionnaires. Data analysis techniques using PLS (Partial Least Square). The results of the study show that work-life balance has a positive effect on job satisfaction, while emotional exhaustion harms job satisfaction.